The Effect of Service Quality and Price on Customer Satisfaction - Mohamad Fahrul Azis; Dudi Haryadi (Almana : Jurnal Manajemen dan Bisnis, 2022)
To be able to compete, companies must be able to get as many consumers as possible and retain their customers. To be able to retain customers, companies must improve the things that make customers less or not. Customer satisfaction of service companies is closely related to the quality of service and the prices offered by the company. The purpose of this study was to determine and analyze how the condition of service quality, price, and customer satisfaction in the Workshop Division of PT. Wahana Sun Hutama Bandung and to find out and analyze the influence of Service Quality and Price on Customer Satisfaction. The analytical method used is descriptive and verification methods with a quantitative approach. The results showed that the quality of service was in the fairly good category, the price was in the fairly good category and satisfaction was in a good category. PA partial test shows that service quality has an effect on customer satisfaction and the price has an effect on customer satisfaction. While in the simultaneous test, service quality and price affect customer satisfaction.